The Effect of Direct Learning Model with Routine Practice on Self-Efficacy and Student Learning Outcomes - Syahrastani Syahrastani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This research was conducted because Self-Efficacy and Student Learning Outcomes are still weak. The direct learning model with routine practice is thought to be a factor influencing the Self-Efficacy and Student Learning Outcomes of students in higher education. This study aims to determine how the direct learning model with regular practice affects student self-efficacy and swimming learning outcomes. This type of research is a quantitative correlation with the research population is 90 students who take swimming courses in Higher Education. The research sample was selected by purposive random sampling. The instrument used is a questionnaire, because it is an effective data collection method to test the variables to be measured and the answers expected by the respondents. The questionnaire uses a Likert scale by providing an opportunity to answer each item. Hypothesis testing was carried out with the SPSS 26.0 program using correlational analysis. The results showed that the use of a direct learning model with regular practice will increase students' self-efficacy, as well as improve learning outcomes in swimming lessons.